Spatial disparities of HIV prevalence in South Africa. Do sociodemographic, behavioral, and biological factors explain this spatial variability? - Ugwu, Chigozie Louisa J.; Ncayiyana, Jabulani R. (Frontiers in Public Health, 2022)
Background: In 2021, an estimated 38 million people were living with human immunodeficiency virus (HIV) globally, with over two-thirds living in African regions. In South Africa, approximately 20% of South African adults are living with HIV. Accurate estimation of the risk factors and spatial patterns of HIV risk using individual-level data from a nationally representative sample is invaluable for designing geographically targeted intervention and control programs. Methods: Data were obtained from the 2016 South Africa Demographic and Health Survey (SDHS16). The study involved all men and women aged 15 years and older, who responded to questions and tested for HIV in the SDHS. Generalized additive models (GAMs) were fitted to our data with a nonparametric bivariate smooth term of spatial location parameters (X and Y coordinates). The GAMs were used to assess the spatial disparities and the potential contribution of sociodemographic, biological, and behavioral factors to the spatial patterns of HIV prevalence in South Africa. Results: A significantly highest risk of HIV was observed in east coast, central and north-eastern regions. South African men and women who are widowed and divorced had higher odds of HIV as compared to their counterparts. Additionally, men and women who are employed had higher odds of HIV as compared to the unemployed. Surprisingly, the wealth index was found not to be associated with the HIV status of men. But men who were circumcised had lower odds of HIV (OR 0.47, 95% CI 0.29, 0.77), while those who had STI in the last 12 months prior to the survey had higher odds of HIV (OR 0.47, 95% CI 0.29, 0.77). Conclusion: Spatial heterogeneity in HIV risk persisted even after covariate adjustment but differed by sex, suggesting that there are plausible unobserved influencing factors contributing to HIV uneven variation. This study’s findings could guide geographically targeted public health policy and effective HIV intervention in South Africa.